Genomic analysis of CTX-M-115 and OXA-23/-72 co-producing Acinetobacter baumannii, and their potential to spread resistance genes by natural transformation. (13th April 2022) - Vuillemenot, Jean-Baptiste; Bour, Maxime; Beyrouthy, Racha; Bonnet, Richard; Laaberki, Maria-Halima; Charpentier, Xavier; Ruimy, Raymond; Plésiat, Patrick; Potron, Anaïs
Abstract: Objectives: To characterize Acinetobacter baumannii strains co-producing the ESBL CTX-M-115 and carbapenem-hydrolysing class D β-lactamases (CHDLs), and to assess the potential diffusion of their resistance genes by horizontal transfer. Methods: Nineteen CTX-M-115/CHDL-positive A. baumannii were collected between 2015 and 2019 from patients hospitalized in France. Their whole-genome sequences were determined on Illumina and Oxford Nanopore platforms and were compared through core-genome MLST (cgMLST) and SNP analyses. Transferability of resistance genes was investigated by natural transformation assays. Results: Eighteen strains were found to harbour CHDL OXA-72, and another one CHDL OXA-23, in addition to CTX-M-115, narrow-spectrum β-lactamases and aminoglycoside resistance determinants including ArmA. cgMLST typing, as well as Oxford Scheme ST and K locus typing, confirmed that 17 out of the 18 CTX-M-115/OXA-72 isolates belonged to new subclades within clonal complex 78 (CC78). The chromosomal region carrying the bla CTX-M-115 gene appeared to vary greatly both in gene content and in length (from 20 to 79 kb) among the strains, likely because of IS 26 -mediated DNA rearrangements. The bla OXA-72 gene was localized on closely related plasmids showing structural variations that occurred between pdif sites. Transfer of all the β-lactamase genes, as well as aminoglycoside resistance determinants to a drug-susceptible A. baumannii recipient, was easily obtained in vitro by natural transformation. Conclusions: This work highlights the propensity of CC78 isolates to collect multiple antibiotic resistance genes, to rearrange and to pass them to other A. baumannii strains via natural transformation. This process, along with mobile genetic elements, likely contributes to the considerable genomic plasticity of clinical strains, and to the diversity of molecular mechanisms sustaining their multidrug resistance.